Implementing Microlearning Strategy in Teaching Reading Comprehension Skill - Nurjanah, Ratih Laily (UNIMUS Web Conferences, 2025)
The concept of microlearning strategy is considered helpful to accommodate the modern phenomenon where students have difficulty to stay focus on a thing for a long time. Teaching reading comprehension has become an endless topic to be integrated with various strategies to support students in understanding texts. This study aims to present how microlearning strategy is implemented in teaching reading comprehension skill and describing the students' perceptions on the learning process. The findings present that microlearning strategy was implemented by introducing parts of a paragraph, identifying topic sentence and supporting sentences, identifying main idea of a paragraph, paraphrasing topic sentence, identifying topic of a text, identifying answers based on the questions. Students revealed that microlearning helped them answer questions faster, described main ideas. Microlearning was also mentioned to be useful since it allowed students to study a concept in small parts with flexible time. They also mentioned that it was possible to use microlearning in learning other English skill. These showed that microlearning is recommended for the lecturers and teachers in teaching and learning activities both in the classroom and at home.